Digital Transformation in Enhancing Public Administration Business and Tax Compliance at WTC Tourism Area, South Lampung - Chairian Tomy; Susi Nofitasari; Yasinta Amartiwi; Alfina Zsazsa Naqiya; Risma Pitriani Nuryana (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
This community service program aims to improve digital literacy and tax compliance among micro and small business operators in the WTC (Way Tebing Ceppa) tourism area, South Lampung. The primary issues addressed include the lack of digital financial recording practices and low awareness of tax obligations. Through a participatory approach involving training and mentoring, participants were introduced to digital business tools and basic tax administration. Results show a significant improvement in digital and fiscal knowledge, with increased use of financial recording applications and successful registration of Tax Identification Numbers (NPWP). This initiative supports the development of a transparent, compliant, and technology-adaptive tourism economy.